Identifikasi Miskonsepsi Mahasiswa Calon Guru Fisika Pada Materi Termodinamika Melalui Tes Diagnostik Four Tier Berbasis Web - Ina Yuliana; Putu Widiarini (LPPM Institut Pendidikan Nusantara Global, 2026)
A deep understanding of physics concepts is essential for pre-service teachers, particularly in thermodynamics, which is inherently complex. This study aims to identify students’ misconceptions using a web-based four-tier diagnostic test. The research employed a quantitative approach with a descriptive exploratory method involving 15 students from the Physics Education Program at Universitas Pendidikan Ganesha who had completed the Thermodynamics course. The research instrument consisted of 15 items designed to classify students’ responses into three categories: conceptual understanding, lack of understanding, and misconceptions. The results indicate that misconceptions remain prevalent in several thermodynamics subtopics, particularly the ideal gas law, the First Law of Thermodynamics, thermodynamic processes, and entropy. Most misconceptions were accompanied by high levels of confidence. Additionally, some students provided factually correct answers but demonstrated incorrect conceptual reasoning. These findings suggest that the conceptual understanding of pre-service physics teachers is not yet fully developed and highlight the importance of using diagnostic tests as a basis for designing more effective thermodynamics instruction.